Green marketing and its implications on consumers and businesses in Malaysia - an empirical study - Ahmed, M. I.; Kamalanabhan, T. J.; Chih, Gerald P. L. (Kamla-Raj Enterprises, 2001)
Environmental issues are fast becoming important business issues in Malaysia. Many corporations are beginning to incorporate ‘green values’ into their marketing strategies. Malaysian consumers have been slow in responding to the environmental issues in the past but with increased per capita income and higher education the attitude is changing rapidly. This study was undertaken to find out the level of understanding of the concepts of green marketing and green products among consumers and marketers in Malaysia. Data was collected from 150 respondents using a questionnaire method. Mutivariate statistics was used to analyse the data. The research also evaluated the “green corporations” and their role and responses to the green revolution. The results of the study showed that there is a high degree of environmental awareness among the consumers.